Seroprevalence of West Nile Virus specific IgG and IgM antibodies in North-Western and Western provinces of Zambia - Mweene-Ndumba, Idah (Afr Health Sci, 2015)
BACKGROUND: West Nile Virus (WNV) infection has been reported worldwide, including in Africa but its existence in Zambia is unknown. Symptoms for the virus include headache, myalgia, arthralgia and rash. OBJECTIVES: This study aimed to determine the seroprevalence of WNV and its correlates. METHODS: A cross sectional study was conducted in North-Western and Western provinces of Zambia. Samples were subjected to IgG and IgM antibodies testing against WNV. Logistic regression analyses were conducted to determine magnitudes of association. RESULTS: A total of 3,625 of persons participated in the survey out of which 10.3% had WNV infection. Farmers were 20% (AOR=0.80; 95% CI [0.64, 0.99]) less likely to have infection compared to students. Meanwhile participants who lived in grass roofed houses were 2.97 (AOR=2.97; 95% CI [1.81, 4.88]) times more likely to be infected than those who lived in asbestos roofed houses. IRS was associated with reduced risk of infection (AOR=0.81; 95% CI [0.69, 0.94]). Travelling to Angola was associated with the infection [AOR=1.40; 95% CI [1.09, 1.81]. CONCLUSION: Spraying houses with insecticide residual spray would minimize mosquito-man contact. Furthermore, surveillance at the border with Angola should be enhanced in order to reduce importation of the virus into the country.